INTEGRASI ARTIFICIAL INTELLIGENCE (AI) DALAM PEMBELAJARAN: CAPACITY BUILDING GURU SMA KRISTEN YPKPM AMBON - Patty, Jusak (DEVELOPMENT: Journal of Community Engagement, 2025)
Digital transformation in education demands enhanced teacher competencies in artificial intelligence utilization, yet implementation faces significant challenges in Eastern Indonesia regions. This community service activity aims to improve teachers' competencies at SMA Kristen YPKPM Ambon in AI technology utilization through comprehensive training approaches as a response to identified institutional needs. The community service methodology employed a systematic four-stage approach including in-depth interviews with the principal for situational analysis, needs assessment of all 25 teachers with mandatory participation, a workshop program design using experiential learning approaches, and evaluation using the Technology Acceptance Model. The workshop was designed in three learning phases: initial resistance, active exploration, and implementative reflection with direct practice focus using ChatGPT and Canva AI. Results demonstrate significant transformation in participants' perceptions and competencies, with all teachers successfully generating AI-based learning content and majority capable of creating digital visual media. Substantial improvements occurred across all technology acceptance dimensions, from perceived usefulness to usage intention. The program successfully facilitated transformation from technology resistance toward active adoption based on actual institutional needs, contributing to AI training model development for educators in archipelagic geographical contexts with technological infrastructure limitations. The systematic documentation provides valuable empirical evidence for professional development policy and program development in the digital education transformation era..